Circadian regulation of fatty acid metabolism in humans: Is there evidence of an optimal time window for maximizing fat oxidation during exercise? - Rubio-Valles, M.; Amaro-Gahete, F. J.; Creasy, S. A.; Ramos-Jiménez, A.; Pérez-León, J. A.; Chávez-Guevara, I. A. (Sports Medicine, 2025)
Exercise training performed at the intensity that elicits maximal fat oxidation improves cardiovascular function and metabolic health while simultaneously reducing visceral adipose tissue in patients with obesity and type 2 diabetes. Indeed, it is currently considered an efficient non-pharmacological approach for the prevention and treatment of cardiometabolic disorders. Over the last 5 years, several studies have reported a diurnal variation in both resting fat oxidation as well as maximal fat oxidation recorded during submaximal intensity exercise. Higher fat oxidation has been recorded during the evening in comparison with the early morning, although this has not been universally observed. If evening exercise increases fat oxidation, then this timing of exercise may be preferable for the reversal of cardiometabolic diseases. However, the physiological and molecular mechanisms behind the circadian regulation of fatty acid metabolism have not yet been fully elucidated. The present review thus aims to describe the circadian rhythmicity of several hormones, metabolites, and enzymes involved in fatty acid mobilization and oxidation. Furthermore, we discuss the relevance of circadian mitochondrial dynamics and oxidative phosphorylation to fatty acid metabolism. To conclude our discussion, we highlight those biological (e.g., age and sex) and lifestyle factors (e.g., sleep quality/disturbances or physical activity) that potentially influence the circadian regulation of fatty metabolism and which therefore should be considered for a tailored exercise prescription.